2016
DOI: 10.1111/obr.12471
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets of developmental exposure to bisphenol A in diabesity: a focus on endoderm‐derived organs

Abstract: Several studies associate foetal human exposure to bisphenol A (BPA) to metabolic/endocrine diseases, mainly diabesity. They describe the role of BPA in the disruption of pancreatic beta cell, adipocyte and hepatocyte functions. Indeed, the complexity of the diabesity phenotype is due to the involvement of different endoderm-derived organs, all targets of BPA. Here, we analyse this point delineating a picture of different mechanisms of BPA toxicity in endoderm-derived organs leading to diabesity. Moving from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 130 publications
(160 reference statements)
0
10
0
2
Order By: Relevance
“…The connection of these metabolites with other pathways related to secondary metabolites (2,3-butanediol, tartrate, glycerate) may suggest an effect on the plants’ secondary metabolism, possibly related to their defence mechanisms, as occurs with embryos exposed to BPA 3943 .…”
Section: Resultsmentioning
confidence: 99%
“…The connection of these metabolites with other pathways related to secondary metabolites (2,3-butanediol, tartrate, glycerate) may suggest an effect on the plants’ secondary metabolism, possibly related to their defence mechanisms, as occurs with embryos exposed to BPA 3943 .…”
Section: Resultsmentioning
confidence: 99%
“…Data from multiple sources have shown that the amount of BPA that humans are exposed to may cause adverse health effects, such as diabetes, obesity, abnormal neuronal behavior, developmental effects, and thyroid and reproductive disorders [58][59][60][61]. This has raised concerns among regulatory agencies all over the world [57].…”
Section: Bisphenol Amentioning
confidence: 99%
“…The stimulation of the AT1 receptor induces vasoconstriction, increases the release of catecholamines and the synthesis of aldosterone (Unger, 2002), stimulates fibrosis and inflammation, and reduces the activity of collagenase and the expression of mitogen-activated protein kinase (MAPK) (Mascolo et al, 2017;Mascolo et al, 2020b). The proinflammatory action of AT1 receptors involves the downregulation of the NADPH oxidase expression in smooth muscle cells, the production of reactive oxygen species (ROS), and the activity of pro-inflammatory transcription nuclear factors like nuclear factor-kappaB (NF-κB) and E26 transformationspecific sequence (Ets) (Marchesi et al, 2008;Porreca et al, 2017). Moreover, these receptors induce the release of tumor necrosis factor-α (TNF-α), the interleukin-6 (IL-6), and the monocyte chemoattractant protein-1 (MCP-1) (Dandona et al, 2007) and shift the macrophage phenotype toward the proinflammatory M1 polarization state (Yamamoto et al, 2011).…”
Section: Classic and Non-classic Raasmentioning
confidence: 99%